Pengaruh Kepatuhan Kesehatan dan Keselamatan Kerja (K3) dan Lingkungan Kerja Fisik terhadap Produktivitas Kerja PT OTA Indonesia - Hilmi, Ahmad Nahid; Sundari, Ocky (Dinasti Research, 2026)
This study aims to analyze the effect of occupational health and safety compliance and the physical work environment on employee productivity at PT. OTA Indonesia. The background of this research is based on the importance of productivity as an indicator of organizational success, along with existing issues related to workplace safety and suboptimal physical work conditions. This study employs a quantitative approach with an explanatory research design. The population consists of 300 production employees, with a sample of 171 respondents determined using the Slovin formula and purposive sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with statistical software. The results show that occupational health and safety compliance has a positive and significant effect on employee productivity. Similarly, the physical work environment also has a positive and significant effect on productivity. Simultaneously, both variables significantly influence employee productivity, contributing 68.8%, while the remaining 31.2% is influenced by other variables outside this study. The findings indicate that improving compliance with occupational health and safety as well as enhancing the physical work environment can optimize employee productivity. This study provides important implications for organizations in managing workplace safety and physical work conditions as strategic factors to improve employee performance